Edge effects on biomass, growth, and tree diversity of a degraded peatland in West Kalimantan, Indonesia - DWI ASTIANI; LISA M. CURRAN; MUJIMAN MUJIMAN; DESSY RATNASARI; RUSPITA SALIM; NELLY LISNAWATY (Society for Indonesian Biodiversity, 2018)
Astiani D, Curran LM, Mujiman, Ratnasari D, Salim R, Lisnawaty N. 2018. Edge effects on biomass, growth, and tree diversity of a degraded peatland in West Kalimantan, Indonesia. Biodiversitas 19: 272-278. Tropical forested peatlands in Indonesia are threatened by logging and clearing which reduce their ecosystem functions and degrade the environment. Land use change activities disturbed intact forests, resulted in landscape fragmentation. Scattered forest matrices resulted in forest edge areas, which will considerably affect the forest biotic and abiotic conditions, as well as forest tree dynamics within the edge sites. The goal of this study was to investigate the effect of forest edge on perimeter of the forest fragment on the forest biomass stock, growth, tree basal area as well as species composition, richness and abundance in a degraded peatland forest in West Kalimantan. A twelve-ha forest was divided into 35 plots in the interior forest and 13 at the forest edge; each plot was 50 m by 50 m in size based on their abiotic conditions such as light and temperatures. Leaf Area Index (LAI) was measured in each plot of both forest edge and interior sites using Licor-2100. The results indicated that even though the biomass levels maintained relatively moderate to high levels on both sites, forest edge significantly lowered forest biomass by 32%, reduced 23-25% of tree-biomass growth per unit area for both tree diameter of 10-20 cm and >20 cm. There was a shift of tree species composition, 76 species were found on both sites, 24 species were not found in edge site, but present in the interior site and 10 species were found only in edge site. Peatland forest matrix created forest edges that are lowering peatland forest roles in sequestering carbon per unit area and reducing species diversity. Peatland forest restoration should be conducted to reduce forest matrices and to lower the edge effects.